EMOCREA and educational inspection: realities and challenges - Antonio F.,; Batista Espinosa, Francisco J.; Kostiv, Elena (Avances en Supervisión Educativa, 2022)
The area of "Emotional Education and Creativity" (EMOCREA) was born in the Canary Islands with the intention of implementing a compulsory curriculum that favors the acquisition of emotional and creative skills in Primary Education students, as a response to the new challenges imposed by the complex, adverse and uncertain society, that we have had to live. The objective of this work is to offer a set of arguments that justify the relevance of this curricular innovation, together with the assessment made by a sample of 16 educational inspectors on its implementation, collected through a questionnaire designed for this purpose. All this in order to offer guidance to the education inspectorate so that it can effectively develop the supervision and support that the process of accompanying teachers requires on the path towards a school that educates from the emotional heart.
Keywords: emotional education; creativity education; educational inspection; educational supervision; counselling